Integration of Islamic Values in Modern Pedagogy: A Comparative Effectiveness Study - Nurul Iman, Aziz (Islamic Journal of Teaching and Learning, 2025)
This study examines the integration of Islamic values into modern pedagogical approaches in secondary schools across Indonesia, Malaysia, and Saudi Arabia. The research addresses the gap in empirical evidence on synthesizing Islamic educational philosophy with contemporary teaching methods to enhance both academic performance and character development. Using a mixed-methods design, the study compared three pedagogical approaches—traditional Islamic education, modern secular pedagogy, and an integrated Islamic-modern approach—among 720 students from 12 schools. Data were collected through validated instruments for academic and non-academic outcomes, combined with classroom observations and interviews. Results demonstrated that the integrated approach significantly outperformed traditional and modern methods across all outcome domains, including academic achievement, critical thinking, moral reasoning, spiritual development, and student engagement. The integration facilitated meaningful connections between religious values and academic content, fostering intrinsic motivation and holistic development. These findings provide valuable insights for curriculum reforms, teacher training, and educational policy in Muslim educational contexts globally.